2017
DOI: 10.1080/15548627.2017.1385677
|View full text |Cite
|
Sign up to set email alerts
|

Centrosome to autophagosome signaling: Specific GABARAP regulation by centriolar satellites

Abstract: Yeast have one Atg8 protein; however, multiple Atg8 orthologs (LC3s and GABARAPs) are found in humans. We discovered that a population of the Atg8 ortholog GABARAP resides on the centrosome and the peri-centrosomal region. This centrosomal pool of GABARAP translocates to forming autophagosomes upon starvation to activate autophagosome formation in a non-hierarchical pathway. How this centrosome-to-phagophore delivery of GABARAP occurs was not understood. To address this, we have shown that the archetypal centr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…As prophase progresses to prometaphase, the nuclear envelope dismantles, microtubules are extended to the exposed chromatin and the centrosomes, the nucleation sites from where the tubulin filaments grow and travel to the opposing ends of the chromatin to form the mitotic spindle (Dey and Baum, 2021). Centrosomes serve as the main microtubuleorganizing centers of the cells and several autophagy-regulating proteins including microtubule-associated proteins 1 light chain 3B (LC3B), gamma-aminobutyric acid receptor-associated protein (GABARAP), sequestesome-1 and WD repeat domain phosphoinositide-interacting protein 2 (WIPI2) and have been detected at the centrosome region in mitotic cells (Joachim and Tooze, 2017;Holdgaard et al, 2019). Interestingly, a FIGURE 1 | Cell cycle-dependent switch of autophagic master regulator.…”
Section: Targeted Autophagy Stabilizes Centrosomesmentioning
confidence: 99%
“…As prophase progresses to prometaphase, the nuclear envelope dismantles, microtubules are extended to the exposed chromatin and the centrosomes, the nucleation sites from where the tubulin filaments grow and travel to the opposing ends of the chromatin to form the mitotic spindle (Dey and Baum, 2021). Centrosomes serve as the main microtubuleorganizing centers of the cells and several autophagy-regulating proteins including microtubule-associated proteins 1 light chain 3B (LC3B), gamma-aminobutyric acid receptor-associated protein (GABARAP), sequestesome-1 and WD repeat domain phosphoinositide-interacting protein 2 (WIPI2) and have been detected at the centrosome region in mitotic cells (Joachim and Tooze, 2017;Holdgaard et al, 2019). Interestingly, a FIGURE 1 | Cell cycle-dependent switch of autophagic master regulator.…”
Section: Targeted Autophagy Stabilizes Centrosomesmentioning
confidence: 99%
“…In this context, it is tempting to speculate that CS are able to sequester compromised or superfluous centrosomal proteins that are subsequently targeted for autophagic destruction. However, additional work suggested that PCM1 retains GABARAP in an inactive state at CS, and it is also plausible that CS act to adjust autophagic flux by releasing the “dormant” CS-associated GABARAP pool to the centrosome [ 12 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has also been suggested that CS, at a distance from the centrosome, keep protein degradation machinery away from centrosome to prevent untimely ubiquitination and degradation of centrosomal components 14 . In fact, CS have been linked to ubiquitination, autophagy and the control of proteolysis in the cell [50][51][52][53][54][55][56] . Consequently, we believe that positioning CS closer to the centrosome in Kif9 depleted cells, in turn, positions the proteolytic machinery closer to centrosome-associated substrates leading to excess proteolysis.…”
Section: Kif9 Depletion Phenotypes In Mitosis Can Be Rescued By Inhib...mentioning
confidence: 99%